A rare case of pancraniosynostosis observed in a historical skull from the 19 th century cranial collection named “Królestwo Polskie” (“Polish Kingdom”) - Cieślik, Agata; Nowaczewska, Wioletta; Kołtowska, Anna; Henneberg, Maciej (Anthropological Review, 2021)
Rare diseases are a challenge in paleopathological research, mainly due to the ambiguity of skeletal signs, bad preservation state of the material, and lack of the reference material. The aim of our article is to present the skull characterized by the decreased values of the metrical traits and numerous pathological features of the cranial morphology and make an attempt to determine the possible cause of the observed anomalies. The subject of our study is a cranium No KP 131 belonging to Polish skeletal collection named „Polish Kingdom”. We used both standard anthropometric methods, as well as the imaging techniques to detect the probable causes of the observed pathological changes. This specimen presents a complex of pathologies. Decreased values of the metrical features, thinning of the lateral walls of the neurocranium and the presence of platybasia were probably caused by premature closure of all main cranial sutures. Pathologies observed in cranium No 131 XIX might have had a common cause in some form of syndromic disorders.